2015
DOI: 10.5688/ajpe79109
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality Among Pharmacy Students

Abstract: Objective. To determine the quality of sleep among pharmacy students in the didactic portion of the curriculum at one school of pharmacy. Methods. The study consisted of an anonymous, voluntary survey that included the Pittsburgh Sleep Quality Index (PSQI), a self-rated instrument that measures sleep habits for a month. Results. The survey was completed by 253 students. Students in the lower grade point average (GPA) category had higher scores on 2 of 7 components of the PSQI and on the global score. Poor slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 23 publications
5
44
2
8
Order By: Relevance
“…This is consistent with some other studies that found a significant association between gender and the poor sleep quality (Cheng et al 2012). The third-year students did, however, have the lowest numerical mean global PSQI score and lowest prevalence of poor sleepers (Cates et al 2015). Furthermore, short sleep appeared to be more common among minority race/ethnic groups, although the association was not significant (Whinnery et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with some other studies that found a significant association between gender and the poor sleep quality (Cheng et al 2012). The third-year students did, however, have the lowest numerical mean global PSQI score and lowest prevalence of poor sleepers (Cates et al 2015). Furthermore, short sleep appeared to be more common among minority race/ethnic groups, although the association was not significant (Whinnery et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cates and colleagues gathered self-reported, anonymous grade-point averages from student pharmacists and administered them the Pittsburgh Sleep Quality Index. 23 The latter authors also discovered widespread poor sleep quality (at a level similar to postpartum mothers with infants), especially for students with lower self-reported GPAs. In the same study, female pharmacy students reported less difficulty with maintaining sleep durations than male students.…”
Section: Introductionmentioning
confidence: 91%
“…Studies of the quality of sleep of Lithuanian students using the Pittsburgh sleep quality index have shown the prevalence of sleep disturbances at institutions of higher education vary somewhat between 58.1 % and 74.1 % (Preišegolavičiūtė et al, 2010;Proškuvienė et al, 2007;Mikaliūkštienė et al, 2012). Studies by researchers in other countries show that between 39 % and 68.6 % of students suffer from poor sleep (Cates et al, 2015;Lopes et al, 2013;Lund et al, 2010). Some authors emphasize there is still a lack of epidemiological information about the association between sleep disturbances and simultaneously evaluated the comorbid relationships of sleep in the general population and in discrete highrisk populations, for example, in groups of college and higher-education students (Veldi et al, 2005;Eller et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…socialinių mokslų studentų. Palyginę gautus miego sutrikimų rezultatus su kitų autorių Lietuvoje ir užsienio šalyse atliktais tyrimais taikydami Pitsburgo miego kokybės indeksą pastebime, kad miego sutrikimų paplitimas yra gana panašus (Preišegolavičiūtė et al, 2010;Proškuvienė ir kt., 2007;Cates et al, 2015;Lund et al, 2010). Tai, kad toks didelis procentas studentų turi miego sutrikimų, gali lemti ir tyrėjų interesas tyrinėti didžiausią riziką turinčius studentus, pavyzdžiui, medicinos, farmacijos, teisės ar ekonomikos specialybių.…”
Section: Rezultatų Aptarimasunclassified
See 1 more Smart Citation